2011
DOI: 10.1007/s00709-011-0291-4
|View full text |Cite
|
Sign up to set email alerts
|

Emerging trends in research on spatial and temporal organization of terpenoid indole alkaloid pathway in Catharanthus roseus: a literature update

Abstract: Catharanthus roseus (The Madagaskar Periwinkle) plant is commercially valued for harbouring more than 130 bioactive terpenoid indole alkaloids (TIAs). Amongst these, two of the leaf-derived bisindole alkaloids-vinblastine and vincristine-are widely used in several anticancer chemotherapies. The great pharmacological values, low in planta occurrence, unavailability of synthetic substitutes and exorbitant market cost of these alkaloids have prompted scientists to understand the basic architecture and regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 116 publications
0
41
0
1
Order By: Relevance
“…Extensive studies have revealed that more than 130 TIAs are produced from the central precursor strictosidine in C. roseus ( Fig. 1) (9).…”
mentioning
confidence: 99%
“…Extensive studies have revealed that more than 130 TIAs are produced from the central precursor strictosidine in C. roseus ( Fig. 1) (9).…”
mentioning
confidence: 99%
“…Recent advances in transcriptomics and proteomics have led to the identification of genes and enzymes involved in MIA biosynthesis. Detailed analyses of the expression patterns of MIA biosynthesis genes indicated that at least four cell types in the leaf, i.e., IPAP, epidermal cells, laticifers, and idioblasts, are involved in MIA biosynthesis (De Luca et al 2014;Verma et al 2012), as illustrated in Figure 2B. This indicated the existence of mechanisms for intercellular trafficking of pathway intermediates, i.e., loganic acid from the IPAP to the epidermis and 16-methoxytabersonine from the epidermis to the laticifers and idioblasts.…”
Section: Mia Transport In Catharanthus Roseusmentioning
confidence: 96%
“…Molecular and cellular studies of alkaloid biosynthesis have revealed that enzymes and metabolites related to the same alkaloid biosynthetic pathways do not necessarily co-localize at the tissue, cellular, and subcellular level, implying that alkaloids and their biosynthetic intermediates are dynamically transported in plant tissues (Shitan and Yazaki 2007;Verma et al 2012). Three modes of alkaloid transport exist: inter-organ, intercellular, and intra-cellular (Shitan and Yazaki 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason might be found in the incredibly complex spatiotemporal organisation of metabolism. Using the example of the precious Madagascar Periwinkle alkaloid vinblastine Verma et al (2012) in the current issue summarise the state of the art and discuss how at least four cell types (epidermis, internal phloëm associated parenchyma, laticifers and idioblasts) and five intra-cellular compartments (chloroplast, vacuole, nucleus, endoplasmic reticulum and cytosol) have to cooperate to produce a total of more than 130 bioactive terpenoid indole alkaloids and provide an important base on new strategies to get access to these compounds that have great pharmacological value, are only scarcely produced in planta, cannot be synthetically substituted and therefore are traded at exorbitant market costs.…”
mentioning
confidence: 99%